An Analysis of the Effectiveness of Samsat J'bret Service (West Java Ngabret) during the Covid-19 Pandemic to Improve the Tax Compliance of Motorized Vehicles at the Office of Samsat Bekasi City - Wuwuh Andayani; Septa Prayoga; Mainita Hidayati (Ilomata International Journal of Tax and Accounting, 2022)
Taxes, both central and local taxes, are the main source of income for the state. One of the regional taxes is the Motorized Vehicle Tax (PKB) which is one source of income expected to help local governments in increasing Locally-Generated Revenue (PAD). This has prompted local governments to innovate tax payment services for motorized vehicles by utilizing increasingly advanced information technology which serves as an effort to break the chain of the spread of Covid-19. This study was conducted to analyze the effectiveness of the J’bret (West Java Ngabret) Samsat service system to improve taxpayer compliance in paying the motorized vehicle tax during the Covid-19 pandemic in Bekasi City, the obstacles that emerged, and the efforts made by the Samsat and taxpayers in realizing the effectiveness of the service system. The research method was a qualitative approach by employing a descriptive approach. The results of this study indicated that the J’bret Samsat service system has been effective and fully following the theory of effectiveness aspects according to Muasaroh (2013). Last, what needs to be improved was more campaigns held for taxpayers about the existence of a motorized vehicle tax payment service system through the Samsat J’bret.